1998
DOI: 10.1021/bi980606o
|View full text |Cite
|
Sign up to set email alerts
|

Benzo[a]pyrene Enhances the Formation of 8-Hydroxy-2‘-deoxyguanosine by Ultraviolet A Radiation in Calf Thymus DNA and Human Epidermoid Carcinoma Cells

Abstract: The objective of this study is to investigate if benzo[a]pyrene (BaP) and ultraviolet (UV) radiation synergistically induce oxidative DNA damage. Calf thymus DNA was incubated with BaP and irradiated with UVB (280-320 nm) and UVA (335-400 nm). BaP substantially enhanced the formation of 8-hydroxy-2'-deoxyguanosine (8-OHdG) by UVA, but only moderately increased the level of 8-OHdG by UVB. Formation of 8-OHdG proportionally correlated with both UV dose and BaP concentration. Human epidermoid carcinoma cells were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 29 publications
2
54
0
Order By: Relevance
“…Exposure of mammalian cells to B[a]P and fluorescent light induces 3-10 fold more 8-hydroxyguanine formation than it is carried out with B[a]P but without light (113). A similar observation by UVA light irradiation of B[a]P mixture with calf thymus DNA or with cultured human epidermoid carcinoma cells was reported by another group (145). These studies also points to the involvement of superoxide anion during the oxidation of guanine.…”
Section: Other Dna Damages By the Combination Of Light And Pahssupporting
confidence: 74%
“…Exposure of mammalian cells to B[a]P and fluorescent light induces 3-10 fold more 8-hydroxyguanine formation than it is carried out with B[a]P but without light (113). A similar observation by UVA light irradiation of B[a]P mixture with calf thymus DNA or with cultured human epidermoid carcinoma cells was reported by another group (145). These studies also points to the involvement of superoxide anion during the oxidation of guanine.…”
Section: Other Dna Damages By the Combination Of Light And Pahssupporting
confidence: 74%
“…The level of 8-OHdG adduct formed in cultured cells was much higher than that in calf thymus DNA. These results suggest that the metabolites of benzo[a]pyrene exhibit higher capability in induction of 8-OH-dG [65]. The subsequent study revealed that its metabolite, benzo[a]pyrene bay-region diolepoxide combined with UVA synergistically induced 8-OHdG in a level about 25-fold higher than benzo[a]pyrene.…”
Section: Formation Of 8-hydroxyguanine (8-ohdg) Adductmentioning
confidence: 87%
“…Liu et al reported that benzo[a]pyrene enhances the formation of 8-OHdG formation by UVA radiation in calf thymus DNA and cultured cells [65]. The level of 8-OHdG adduct formed in cultured cells was much higher than that in calf thymus DNA.…”
Section: Formation Of 8-hydroxyguanine (8-ohdg) Adductmentioning
confidence: 99%
“…Thus, the combined impact of these 2 environmental factors at subcarcinogenic doses remains a challenging subject. Our previous studies demonstrated that the combination of BaP and UVA synergistically induced oxidative DNA damage in vitro 13 and in vivo 14 and BPDE-DNA adducts in vivo.…”
mentioning
confidence: 99%